Analisis Kemampuan Pemecahan Masalah Siswa SMP Kristen Satya Wacana Salatiga pada Materi Garis dan Sudut - Denilson Ndaong; Fika Widya Pratama (Journal on Education, 2023)
Problem-solving abilities are essential for solving everyday problems, so the aims of this research is to analyse the problem-solving ability of class VIIIA students at Satya Wacana Christian Junior High School, Salatiga. This research was done in the odd semester of the 2022/2023 academic year. The type of this research is descriptive qualitative research. Three subjects were selected by a purposive sampling technique based on the level of student learning outcomes. This research used written tests and interviews. The written test given was three essay questions about lines and angles that have been validated by three validators. The triangulation used is triangulation technique. This research concludes that students' problem-solving abilities are as follows: the students with high and moderate learning outcomes can understand the problems, devise plans and carry out the plans even though they can not look back. Whereas the student with low learning outcomes can understand the problem and devise plans, but can not carry out the plans and look back.